Sclerosing pneumocytoma with metastasis to the mediastinal and regional lymph nodes - Xiaojun Wang; Lizhi Zhang; Yanfu Wang; Xuzhao Jia; Jiali Wang; Hua Zhang (Wolters Kluwer Medknow Publications, 2018)
Sclerosing pneumocytoma (SP) is an uncommon benign tumor, and metastasis of SP has been rarely reported. Here, we report the case of a 26-year-old woman with surgically confirmed SP. The tumor diameter was 40 mm, and metastasis to mediastinal and regional lymph nodes was observed. Immunohistochemically, both surface and round cells were positive for epithelial membrane antigen, thyroid transcription factor 1, and vimentin. Only surface cells expressed creatine kinase, carcinoembryonic antigen, napsin A, and cytokeratin 7, and only round cells expressed progesterone receptor. Ki-67 was detected in ~3% of cells, and the rate of weak positive p53 staining was 3%. Both cell types were negative for chromogranin A, synaptophysin, CD3, and CK20. Multiple metastases in a young SP patient are very rare, and potential mechanisms of metastasis may be related to epithelial-mesenchymal transformation.